2022
DOI: 10.21203/rs.3.rs-1549156/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new perspective on increased emergence of Central Pacific ENSO in the recent two decades

Abstract: In this study, we provide a new perspective on the recent increased emergence of the central Pacific type of El Niño and Southern Oscillation (ENSO). Our results indicate that early-spring Aleutian Low (AL) intensity has a remarkable impact on the following winter ENSO especially after the late-1990s. Decrease (increase) in the early-spring AL strength tends to induce an anomalous cyclone (anticyclone) over subtropical North Pacific via wave-mean flow interaction. The anomalous cyclone (anticyclone) leads to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Meanwhile, we found that SST anomaly in tropical Pacific can lead to circulation anomaly in the North Pacific, similar to the previous studies that El Niño (La Niña) results in the strengthening (weakening) of the Aleutian Low (Straus & Shukla, 2000). Chen et al (2023aChen et al ( , 2023b found that the decreased (increased) Aleutian Low during spring can lead to anomalous cyclones (anticyclones) over the subtropical, influencing El Niño (La Niña) in the tropical central Pacific. As a result, it is important to find out the changes in the relationship between tropical Pacific SST and North Pacific circulation under the interdecadal variations of tropical Pacific SST.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, we found that SST anomaly in tropical Pacific can lead to circulation anomaly in the North Pacific, similar to the previous studies that El Niño (La Niña) results in the strengthening (weakening) of the Aleutian Low (Straus & Shukla, 2000). Chen et al (2023aChen et al ( , 2023b found that the decreased (increased) Aleutian Low during spring can lead to anomalous cyclones (anticyclones) over the subtropical, influencing El Niño (La Niña) in the tropical central Pacific. As a result, it is important to find out the changes in the relationship between tropical Pacific SST and North Pacific circulation under the interdecadal variations of tropical Pacific SST.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…In addition, the anomalous Rossby wave train activity originating from the tropical Pacific caused by SST anomaly alters the large-scale circulation patterns in the North Atlantic, leading to the most significant tropospheric warming over northeastern Canada and Greenland, which in turn brings anomalous changes in sea ice in the Arctic (Ding et al, 2014;Wu et al, 1997;Yeh et al, 2018). Additionally, recent studies have indicated that Arctic SIC anomalies could significantly affect tropical climate systems, such as ENSO and tropical cyclone activity (Chen et al, 2020(Chen et al, , 2023a(Chen et al, , 2023b.…”
mentioning
confidence: 99%
“…3), the changes in the correlations with East Asian precipitation seem minor in the developing phase of ENSO (Figure 4a–c), and the correlations become more appreciable in the mature and decay phases of ENSO (Figure 4d–f). The difference may be related to the interdecadal variations of ENSO and its impacts on seasonal precipitation in East Asia in the recent two decades or so (Chen et al, 2022; Hu et al, 2020a; Wu & Mao, 2016, 2018).…”
Section: Seasonality Of Enso Impactmentioning
confidence: 99%
“…Following the interdecadal shift of ENSO properties that occurred in 1976/1977, another regime shift happened in 1999/2000 that featured a decrease in the ENSO variability and an increase in the ENSO frequency (Chen et al, 2022; Hu et al, 2020a). The regime shift concurs with an enhanced zonal gradient of the mean state of SST, a westward shift in the atmosphere–ocean coupling in the tropical Pacific, and an increase in the static stability of the troposphere (Hu et al, 2020a).…”
Section: Seasonality Of Enso Impactmentioning
confidence: 99%
See 1 more Smart Citation